Ludiek tot keihard : studenten voor demokratizering, akademiejaar '78-'79 - Alliët, Patrick; Colruyt, Lieve; Hermans, Ron; Rubbens, André (Berchem : EPO, 1980)
Bibliotheek Patrick Engelbrecht
Nederlands
Monografie